Implementasi Saluran Distribusi Pada PT Surya Donasin - Ramdani, Muhamad Ridwan; Nurendah, Yulia; Sulistiono, Sulistiono (Program Vokasi dan LPPM IBI Kesatuan, 2024)
Distribution channels play a very important role in the success of a company's marketing. because distribution is the spearhead of the company in marketing products or services. Products reach consumers directly or indirectly through distribution channels. In choosing the most appropriate distribution channel to use, the company must be in accordance with the conditions and objectives of the company. Distribution channels are the core of the company's efforts to distribute goods from producers to consumers. The author's purpose of this study is to find out: 1) Implementation of distribution channels at PT Surya Donasin, 2) What are the obstacles to implementing distribution channels at PT Surya Donasin, 3) Efforts to deal with obstacles to implementing distribution channels at PT Surya Donasin. The results of the review conducted, 1) The distribution channel carried out by PT Surya Donasin uses an intensive distribution channel to obtain a wider market. 2) Constraints in implementing distribution channels, namely, market potential that has not been covered, payment administration that does not match the specified time, lack of human resources and facilities to support the distribution process, procurement of goods that are often out of stock. 3) Efforts to overcome obstacles, namely, the Supervisor makes visits to check each store, checks stores that still have bills that are past the payment time, adds resources and facilities as needed, always maintains inventory so that out of stock does not occur Keywords: distribution channels, implementation, marketing